2020
DOI: 10.1111/modl.12677
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical and Lexical Development During Short‐Term Study Abroad: Exploring L2 Contact and Initial Proficiency

Abstract: This study examined linguistic development among both intermediate and advanced college-level second language (L2) learners during short-term study abroad summer programs in Spain. Participants completed a measure of overall proficiency, as well as assessments of receptive grammatical (morphosyntactic) and lexical (semantic) abilities at the beginning and end of their programs. They also reported their use of and exposure to the target language on a weekly basis while abroad. Analyses explored (a) whether lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 62 publications
(116 reference statements)
2
41
4
Order By: Relevance
“…Increased opportunities to interact in the target language have often been considered as a catalyst for facilitating oral production development (Llanes 2011). Regarding lexical gains, it has been shown that increased L2 contact can result in more native-like lexical use (Foster 2009) and that even short term intensive L2 immersion can be beneficial for lexical and semantic acquisition (e.g., Cubillos et al 2008;Issa et al 2020;Llanes 2011;Llanes and Muñoz 2009;Pliatsikas and Chondrogianni 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased opportunities to interact in the target language have often been considered as a catalyst for facilitating oral production development (Llanes 2011). Regarding lexical gains, it has been shown that increased L2 contact can result in more native-like lexical use (Foster 2009) and that even short term intensive L2 immersion can be beneficial for lexical and semantic acquisition (e.g., Cubillos et al 2008;Issa et al 2020;Llanes 2011;Llanes and Muñoz 2009;Pliatsikas and Chondrogianni 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research on long-term study abroad has found that the learners' productive skills in the target language benefit significantly from this experience. For example, gains in language production can be seen in higher fluency (e.g., Segalowitz and Freed 2004;Mora and Valls-Ferrer 2012;Segalowitz and Freed 2004), grammar accuracy (e.g., Collentine 2004;Issa et al 2020), better pronunciation (Nagle et al 2016;Wright and Zhang 2014), and more a stable intonation (Henriksen et al 2010;Craft 2015). In addition, accelerated rates of lexical development seem to be one of the most significant gains of study abroad (Milton and Meara 1995;Collentine 2004), which have been attested in increased lexical fluency (e.g., Kim et al 2015), pronunciation (e.g., Díaz-Campos 2004;Lord 2006), as well as complexity and richness (e.g., Serrano et al 2011Serrano et al , 2012.…”
Section: L2 Exposure and Lexical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by the studies in the previous section, interactions with TL speakers, such as those that occur during SA, are critical to the L2 acquisition of stylistic and regional variation; however, quantifying and characterizing interactions between learners and TL speakers remains a complex task for researchers in SLA and LVC alike. For example, a number of studies on L2 acquisition during SA have sought to capture total language contact (speaking, reading, writing, listening) during SA using the Language Contact Profile (LCP; Freed et al., 2004), but most have not been able to establish a significant correlation between the LCP score and proficiency gains during SA (Isabelli–García, 2010; Issa et al, 2020; Magnan & Back, 2007; Segalowitz & Freed, 2004; cf. Hernández, 2010).…”
Section: Social Network and L2 Acquisition During Study Abroadmentioning
confidence: 99%